Search for ZZ and Zγ* production in pp̄ collisions at s=1.96TeV and limits on anomalous ZZZ and ZZγ* couplings - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We present a study of μμμμ, eeee, and μμee events using 1fb-1 of data collected with the D0 detector at the Fermilab Tevatron pp̄ Collider at s=1.96TeV. Requiring the lepton pair masses to be greater than 30 GeV, we observe one event, consistent with the expected background of 0.13±0.03 events and with the predicted standard model ZZ and Zγ* production of 1.71±0.15 events. We set an upper limit on the ZZ and Zγ* cross section of 4.4 pb at the 95% C.L. We also derive limits on anomalous neutral trilinear ZZZ and ZZγ* gauge couplings. The one-parameter 95% C.L. coupling limits with a form-factor scale Λ=1.2TeV are -0.28<f40Z<0.28, -0.31<f50Z<0.29, -0.26<f40γ<0.26, and -0.30<f50γ<0.28. © 2008 The American Physical Society.